10kV+ Rated SiC n-IGBTs: Novel Collector-Side Design Approach Breaking the Trade-Off between dV/dt and Device Efficiency - Almpanis, Ioannis; Evans, Paul; Antoniou, Marina; Gammon, Peter; Empringham, Lee; Undrea, Florin; Mawby, Philip; Lophitis, Neophytos (My University, 2023)
10kV+ rated 4H- Silicon Carbide (SiC) Insulated Gate Bipolar Transistors (IGBTs) have the potential to become the devices of choice in future Medium Voltage (MV) and High Voltage (HV) power converters. However, one significant performance concern of SiC IGBTs is the extremely fast collector voltage rise (dV/dt) observed during inductive turn-off. Studies on the physical mechanisms of high dV/dt in 4H-SiC IGBTs revealed the importance of collector-side design in controlling the phenomenon. In this paper we propose a novel collector-side design approach, which consists of four n-type layers with optimized doping densities and allows the control of dV/dt independently from the device performance. Further, we demonstrate a reduction of dV/dt by 87% without degrading the high switching frequency capability of the device, or the on-state performance, through the addition of two n-type epitaxial layers in the collector side, between the buffer and the drift regions.
Keywords: design optimization; dV/dt; electromagnetic interface; SiC IGBT; trade-off curves